Efficiency evaluation of phospholipid fatty acid method based on lipid standards: methanol failed to recover a majority of phospholipids yet eluted unexpected glycolipid - Zhang, Shanshan; Jiao, Xinyu; Kang, Hongzhang; Yu, Wenjuan (Frontiers in Microbiology, 2025)
Phospholipid fatty acid (PLFA) method has been popular and powerful for characterizing soil microbial communities over decades. However, little is known about efficiencies of acidic vs. alkaline extractants and catalysts in PLFA extraction and methylation. More urgently, it remains unclear whether methanol could efficiently elute phospholipids while avoiding recovering non-target lipids. Here, by adding pure lipid standards representative of major neutral, glyco-, and phospholipids into acidic and alkaline soils collected from subtropical China, we comprehensively evaluated efficiencies of extraction, elution, and methylation of three steps in the PLFA method. A good proportion of PLFAs could be extracted by phosphate buffer with both acidic (42–51%) and alkaline (43–68%) soils while citrate buffer worked better for acidic (43–46%) than alkaline (36–47%) soils. Phospholipids were expected to be mainly eluted in methanol, yet we found a non-negligible proportion of phospholipids eluted by chloroform for both acidic (36–71%) and alkaline (9–55%) soils, which is much larger than previously reported. Only 42–50% (acidic soils) and 45–68% (alkaline soils) of phospholipids were recovered in methanol. Meanwhile, 16% (acidic soils) and 5% (alkaline soils) of glycolipid DGDG were unexpectedly eluted into methanol. The alkaline catalyst (mean 86% across all investigated phospholipids) was more efficient in facilitating phospholipids methylation than the acidic one (mean 67%). Overall, incomplete separation among lipid types caused loss of phospholipids and introduction of glycolipid interferences in the methanol fraction, leading to biased estimation of soil microbial biomass and composition. Chloroform elution of phospholipids challenges the principle of “like dissolves like” in solid-phase chromatography, although we cannot rule out the uncertainty caused by background PLFAs and future experiments are needed to provide more evidence. To effectively remove lipid interferences and efficiently elute phospholipids, possible solutions include replacing chloroform with hexane, increasing elution volumes of acetone and methanol, and/or using anion exchange columns.